2019
DOI: 10.1159/000501209
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Neuroinflammation in Dengue Viral Disease: Importance of Innate and Adaptive Immunity

Abstract: Neuroinflammation (inflammation in brain) has been known to play an important role in the development of dengue virus disease. Recently, studies from both clinical and experimental models suggest the involvement of neuroinflammation in dengue viral disease. Studies in clinical setup demonstrated that, microglial cells are actively involved in the patients having dengue virus infection, showing involvement of innate immune response in neuroinflammation. It was further proved that, clinical isolates of dengue-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…24 Dengue virus may lead to neuroinflammation by infecting the brain and having either a directly neurotoxic effect or an indirectly neurotoxic effect via systemic inflammation. 25,26 Dengue virus is not generally considered a neurotropic pathogen, but some studies have found dengue virus in the CNS. 27 Clinical evidence indicates that the dengue virus can enter CNS via the hematogenous and axonal transport route 27,28 and infect different neurovascular unit cells, including neuron, microglial, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Dengue virus may lead to neuroinflammation by infecting the brain and having either a directly neurotoxic effect or an indirectly neurotoxic effect via systemic inflammation. 25,26 Dengue virus is not generally considered a neurotropic pathogen, but some studies have found dengue virus in the CNS. 27 Clinical evidence indicates that the dengue virus can enter CNS via the hematogenous and axonal transport route 27,28 and infect different neurovascular unit cells, including neuron, microglial, and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 Microglial cells, such as the immune cells of the CNS, 29 are activated in dengue virus infection, showing the association between dengue virus infection and neuroinflammation. 26 Studies of animal models demonstrated the loss of hippocampus neurons in dengue virus infection, suggesting its long-term effect on learning and memory. 30 Neurocognitive consequences such as memory impairment have been reported in patients with dengue infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of exosomes and other extracellular vesicles in Dengue viral hemorrhagic fever has also been discussed to highlight the importance of exosomal secretion in cytokine storm phenomenon (59). Even viral proteins such as HIV-1 Tat, Nef, and Dengue NS1 circulate in the bloodstream and trigger the generation and transportation of cytokines to multiple organs, including the CNS (73)(74)(75)(76)(77). Ultimately, all these influxes of peripheral inflammatory molecules inside the CNS activate the brain resident macrophages, i.e., microglia, which becomes hyper-activated and starts producing its own set of inflammatory molecules and causes neuroinflammation.…”
Section: Why the Brain Is "The Most Susceptible" For Cytokine Storm?mentioning
confidence: 99%